The Impact of Covid- 19 to Capitalism Economic System: An Islamic Economic and Financial Perspective - Zulhelmy Zulhelmy; Hidayat Hidayat (Perhimpunan Intelektual Muslim Indonesia, 2020)
The purpose of this article is to see how Covid-19 impacts the economy of a country, especially countries that have so far relied on the tourism service business. The research method is based on a literature study about Islamic economics and finance in the Covid-19 pandemic case. The analysis was done based on the facts collected from the literature, considering consistent facts and conclusions based on these facts after an analysis was completed. As a result, many businesses have been forced to stop and lay off their employees. Not to mention the other impacts besides business, namely health and education. The current economy is more dominated by the capitalist economic system, emphasizing the benefits of bringing a country's economic system's fragility. It is undeniable that the capitalist economic system has created prolonged problems, especially in creating social welfare. Even now, the world has seen the economic system's weakness and fragility, which has been used as the basis for economic development in every country, mostly European and western countries, that exist in the capitalist economic system. At the same time, people see an alternative system that has been proven to create social welfare, namely the Islamic economic system. The Islamic economic system has proven to be an anti-crisis system, be it economic, monetary, or financial crises. It is time for the ummah or society to leave the fragile economic system of Capitalism, to be replaced by an Islamic economic system that has been proven both conceptually, historically, and empirically while in a glorious Islamic civilization from the time of the Prophet Muhammad to the time of the Ottoman Turks.